Profile of gender violence by intimate partners - Kronbauer, José Fernando Dresch; Meneghel, Stela Nazareth (Revista de Saúde Pública, 2005)
OBJECTIVE: To investigate the prevalence and profile of gender violence (physical, psychological, and sexual) perpetrated against women by current or former intimate partners. METHODS: This is a cross-sectional study carried out at a primary healthcare unit in the city of Porto Alegre, Southern Brazil. Our sample comprised 251 women aged 18-49 years who attended the healthcare unit between October and November 2003. Data were collected by means of a questionnaire and double-entered into a electronic spreadsheet. We carried out univariate and bivariate analyses and the chi-square test. RESULTS: The prevalence of the three types of violence were: psychological (55%, 95% CI: 49-61), physical (38%; 95% CI: 32-44), and sexual (8%; 95% CI: 5-11). Variables significantly associated with the three types of violence included woman's age (psychological: p=0.004), woman's schooling (psychological and physical; p=0.012 and 0.023, respectively), partner's schooling (p=0.004, 0.000), social class (p=0.006, 0.000), years with partner (p=0.006, 0.005), partner's occupation (p=0.015, 0.001), number of pregnancies (p=0.018, 0.037), and prevalence of minor psychiatric disorders (p=0.000, 0.000). CONCLUSIONS: The present study found high prevalences of gender violence perpetrated by intimate partners among the users of a primary healthcare unit. Such units play an important role in preventing violence against women.